El principio de responsabilidad proactiva: una oportunidad para un mejor cumplimiento de la normativa en materia de protección de datos de carácter personal en el ámbito latinoamericano - Santamaría Ramos, Francisco José (2020)
This study tries to determine whether the principle of proactive liability, established in the European General Data Protection Regulation, can be easily transferred to the Latin American sphere despite the fact that Latin American regulations are excessively fragmented and, in any case, it does not include the principle of proactive responsibility as one to be taken into account in the protection of personal data. This investigation is of a bibliographic type and it approaches to the knowledge of the subject to identify what is known and what not about the object of study. Therefore, the objective is to carry out a synopsis that brings together different investigations, reports and articles that account for the current state of the phenomenon under study; however, such a review also implies making a critical assessment of the research and articles. In this sense, understanding each case examined provides invaluable insights and explanations for understanding the topic of the object of study, and allows proposing strategies to improve the problem, which helps to put the topic in its respective context. The bibliography has been selected both for its usefulness in the present field of study and for itstopicality, seeking to review the most important and current bibliographic material as possible.